Sustainable practices in urban freight distribution in Bilbao - Esther Alvarez; Alberto de la Calle (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The objective of the present study is to select some feasible and sustainable logistic practices in order to improve the urban freight distribution in Bilbao city. Design/methodology/approach: After a thorough literature review and a benchmarking, Analytic Hierarchy Process (AHP) techniques were used in order to support the decision making processes in order to select the most interesting practices. The criteria used for this selection were based on four factors: (1) improvement of the city freight distribution, (2) implementation possibility, (3) short and medium term applicability and (4) impact on the citizens of Bilbao. Findings: The paper identifies some specific problems that must be faced during the last stage of the logistics chain, where products are usually delivered to final customers in the urban environment. Research limitations/implications: Not all good urban freight distribution practices can be applied universally to all types of towns. Therefore, it is necessary to design some practices specifically to each particular city according to the physical characteristics of the city, the companies' motivation and the citizens' habits. Practical implications: All the agents involved in the city freight distribution should be aware of the benefits and problems that their actions cause. Originality/value: This study was carried out from a wide perspective that included researchers, logistics operators and local authorities.
Keywords: 650; AHP; urban freight distribution; last-mile logistics; city